The Use of AI Chatbots in Study Group Learning to Improve Students' Self-Efficacy in Renewable Energy Materials in Class X of High School - Cindy Maulia; Syahril Syahril; Nur Islami (Journal of Education and Learning Research, 2026)
Students’ self-efficacy in learning physics is often still low, particularly in abstract topics such as renewable energy, which leads to low participation and confidence in learning. Therefore, an effective learning approach is needed to improve students’ self-efficacy. This study aims to analyze the effectiveness of Artificial Intelligence (AI)-based chatbots integrated into study group learning to improve students’ self-efficacy. This research used a quasi-experimental method with a nonequivalent control group design conducted at SMAIT Al-Fityah Pekanbaru involving class X students. The sample consisted of 46 students divided into experimental and control classes. Data were collected using self-efficacy questionnaires administered before and after treatment and analyzed using N-Gain, paired sample t-test, and independent sample t-test. The results showed that the average N-Gain in the experimental class (0.57) was higher than in the control class (0.32), both categorized as medium. These findings indicate that the integration of AI chatbots in study group learning is effective in improving students’ self-efficacy and supports more interactive and meaningful learning.